XBREACH OF CONSIGNMENT AGREEMENT BETWEEN ADEE CAKE MANUFACTURER AND SMALL TRADERS (RESEARCH STUDY IN MEUREUDU DISTRICT, PIDIE JAYA REGENCY) - Aisyah; Teuku Yudi Afrizal; Tri Widya Kurniasari (PT. Radja Intercontinental Publishing, 2026)
This study aim For know implementation agreement consignment between manufacturers and traders small cake Adee in the District Meureudu , Pidie Jaya Regency , as well analyze factor reason occurrence default and efforts settlement dispute in agreement The problems studied​​ related with practice agreement consignment in general done in a way oral based on principle trust , so that in implementation cause problem law in the form of delay payment results sales , implementation obligations that are not perfect , or No fulfilled achievements by traders to manufacturer . Research This use method qualitative with approach juridical empirical and nature study descriptive analytical . Research data obtained through interviews , observations , and documentation to manufacturer as well as trader small cake Adee in the District Meureudu , Pidie Jaya Regency , which then analyzed in a way qualitative . Research results show that implementation agreement consignment Still based on trust without agreement written . Causal factors occurrence default covering use results sale For interest personal , condition business traders who experience difficulties , as well as weakness supervision in implementation agreement . Form default that occurred in the form of delay payment , implementation achievements that are not appropriate , and not carry out performance The same once . Completion dispute done non - litigation through deliberation and negotiation For maintain connection Work The same between the parties . It is recommended that producers and traders small make agreement consignment in a way written to provide certainty law for the parties .